Safety and efficacy of bipolar versus monopolar transurethral resection of the prostate in benign prostatic hyperplasia: A comparative study - KC, Hari Bahadur; Sharma, Suman; Adhikari, Rajesh (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Monopolar transurethral resection of the prostate (TURP) is considered the gold standard for surgical management of benign prostatic hyperplasia (BPH). Recently, TURP using bipolar electrocautery is increasingly used with promising results over conventional TURP. The aim of this study was to compare the peri-operative outcomes between monopolar and bipolar TURP. Methods: In this study, patients who underwent TURP between January 2023 and June 2025 were analyzed retrospectively. The patients were divided into two groups: monopolar TURP (n=71) and bipolar TURP (n=116). The parameters including prostate volume, symptoms scores, maximum flow rate (Qmax), resection time, resected tissue weight, decrease in hemoglobin and sodium, and complications were recorded and analyzed. Results: The amount resected prostate tissue was significantly greater in bipolar TURP (19.4±9.4 vs 16.4±7.0 g, p=0.023), although the resection time was comparable between two groups. Bipolar TURP (bTURP) resulted early catheter removal (2.35±0.6 vs 2.77±1.4 days; p=0.007) and shorter hospital stay (4.28±0.6 vs 4.68±0.9 days; p=0.001) than monopolar TURP (mTURP). There was significant decrease in post-operative serum sodium concentrations in mTURP (3.14 ± 3.0 vs 1.5 ± 2.4 mEq/L, p<0.001). The improvement in symptoms, quality of life, Qmax, and complications encountered were similar in two groups. Transurethral resection (TUR) syndrome occurred in one patient in mTURP group whereas none occurred in bTURP group. Conclusions: Bipolar TURP is as effective and safe as monopolar TURP in BPH. Moreover, bipolar resection has the additional advantage of early catheter removal, shorter hospital stay, minimal electrolyte imbalance, and less post-operative morbidity.